2012
DOI: 10.1021/bm300523e
|View full text |Cite
|
Sign up to set email alerts
|

Interplay Between Viscoelastic and Chemical Tunings in Fatty-Acid-Based Polyester Adhesives: Engineering Biomass toward Functionalized Step-Growth Polymers and Soft Networks

Abstract: This Article describes the synthesis and characterization of renewable self-adhesive coatings with tunable viscoelastic properties and equipped with well-defined amounts of carboxylic acid "sticker" groups with adhesion promoting characteristics. Hydroxyl-ended polyesters with various architectures (linear, branched) were synthesized by melt polycondensation of dimerized fatty acids and fatty diols and then cured with maleic anhydride-modified triglycerides (such as maleinized soybean oil) in the presence of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
71
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(74 citation statements)
references
References 44 publications
(59 reference statements)
2
71
0
1
Order By: Relevance
“…It has also been demonstrated that polyesters from dimer acid and diols after being cured with maleic-anhydride-modified plant oils or epoxidized plant oils exhibited PSA properties. 16,17 In our previous study, PSAs were successfully prepared from a mixture of epoxidized fatty acids (EFAs). 18 The mixture of EFAs was prepared from ESO via the selective hydrolysis of the ester groups in ESO.…”
Section: ■ Introductionmentioning
confidence: 99%
“…It has also been demonstrated that polyesters from dimer acid and diols after being cured with maleic-anhydride-modified plant oils or epoxidized plant oils exhibited PSA properties. 16,17 In our previous study, PSAs were successfully prepared from a mixture of epoxidized fatty acids (EFAs). 18 The mixture of EFAs was prepared from ESO via the selective hydrolysis of the ester groups in ESO.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In addition, the PSAs contained hydroxyl groups (-OH) and a small amount of unreacted -COOH groups. The -OH and -COOH groups could improve the wetting of the PSAs on various adherends such as paper, glass, and skin, thus facilitating the intimate contact between the PSAs and the adherends (11,(23)(24)(25). These functional groups in PSAs could also significantly improve the adhesive strength of the PSAs through formations of hydrogen bonds between the PSAs and adherends (23)(24)(25)(26).…”
Section: Copolymerization Of Da With Epoxides and Preparation Of Psasmentioning
confidence: 99%
“…These functional groups in PSAs could also significantly improve the adhesive strength of the PSAs through formations of hydrogen bonds between the PSAs and adherends (23)(24)(25)(26). The -OH and -COOH groups also allowed formations of hydrogen bonds among molecular chains and within the same molecular chain of the PSA, thus increasing the cohesive strength of the PSA (11,(23)(24)(25)(26).…”
Section: Copolymerization Of Da With Epoxides and Preparation Of Psasmentioning
confidence: 99%
See 2 more Smart Citations